Rasionalitas Kebertahanan Migran Urban Bermukim di Kawasan Slum Area Kota Pekanbaru - Hana Salsabilla; Rina Susanti (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
The phenomenon of urban migration is one of the contributors to urban population growth and causes various social challenges, including the emergence of slums. This study examines the rationality of urban migrant survival who choose to settle in the slum area of ​​Sukaramai Village, Pekanbaru City. The theory used is James Coleman's rational choice theory which emphasizes actor decisions based on rational considerations of resources and goals. The research method uses a descriptive qualitative method. Data collection was carried out through observation, in-depth interviews, and documentation. The research subjects consisted of 6 main informants, namely migrant households (newcomers) who live in rented accommodation in the slum area and 1 key informant, namely the RT Head who was selected by purposive sampling. Data were analyzed using the Miles and Hubermas model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the main reasons migrants choose and stay in the area are economic factors, location accessibility, social recommendations, and proximity to markets and workplaces. Although environmental conditions are classified as uninhabitable, migrant communities persist because of rational considerations of available resources